Crimes Committed by Juvenile Delenquents at Barangay Holy Spirit Quezon City: Vol. 5, No. 1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Child In-Conflict with the Law introduces the idea of minor individuals performing illegal activities. Juvenile is anyone under the age of 18 years old and below. A delinquent is a person who breaks the law. Delinquency is a kind of abnormality when an individual deviates from the course of normal social life; this action is called “Delinquency.”Juvenile crime is one of the serious problems not only in the Philippines but also in every country. This problem needs more action from federal, state, and local government officials.The researchers conducted descriptive research to discuss the findings of crimes committed in juvenile delinquency in Barangay Holly Spirit Quezon City. This process gathers all the data to determine what criminal cases they have and the effects of that crime on their personal life. Prevention and awareness should be given to the youths who have committed crimes. This research study was conducted at Barangay Holy Spirit Quezon City. The number of respondents for this study is sixty (60) Police Officers (30) and Barangay Officials in Barangay (30) in Holy Spirit Quezon City.Most of the respondents, both Police officers and Barangay Officials, “Agree” that sa malicious mischieve is the most committed in terms of Felony, illegal possession of a deadly weapon in terms of Offense, followed by a curfew in terms of Infraction. Also, all the respondents “Agree” that Conducting diversion proceedings and assisting in implementing the diversion program for CICL with discernment is the main solution to this problem, while the Absence of family members to attend barangay hearings is the main problem encountered and Implementing a program that can help to parents in guiding their children is the best way to prevent crimes in Barangay Holy Spirit Quezon City.The researchers conclude that all the results of the study are based on the facts gathered from the respondents about the crimes committed by Juvenile Delinquents at Barangay Holy Spirit Quezon City. The data gathered by the researchers are valid and reliable; respondents be described in terms of age, sex, civil status, and educational attainment; there is an effective action to solve the Crimes Committed by Juvenile Delinquent at Barangay Holy Spirit Quezon City and the proposed action that may enhance to apply while assisting the Crimes Committed by Juvenile Delinquent at Barangay Holy Spirit Quezon City.
Keywords: Institutionalization; Psychiatric Illness; Rehabilitation